Aligning values and politics : empowerment versus entitlement - Gendre, Michael; Sánchez, Nicolás (University Press of America, 2016)
This book argues that politics must align with the promotion of self-actualization. Combining private property rights with an ethics of responsibility and drawing from the ideas of Immanuel Kant, the book opens the doors to a nonpartisan analysis of income inequality, inheritance, race relations, abortion and governance.
Keywords: Ethics -- Political aspects -- United States.; Political ethics -- United States.; United States -- Politics and government.; Political participation -- United States.; Transparency (Ethics) in government -- United States.; Political culture -- United States.; Social change -- United States.; Morale -- Aspect politique -- États-Unis.; Morale politique -- États-Unis.; États-Unis -- Politique et gouvernement.; Participation politique -- États-Unis.; POLITICAL SCIENCE -- Essays.; POLITICAL SCIENCE -- Government -- General.; POLITICAL SCIENCE -- Government -- National.; POLITICAL SCIENCE -- Reference.; Political ethics; Political culture; Political participation; Politics and government; Social change; Transparency in government; United States; Electronic book.